Social campaigns in Italian culture of 1970–1980s: advertising and search for national identity - A. A. Ivanova (Концепт: философия, религия, культура, 2020)
This article reviews Italian public service annonncement campaigns of the 1970-1980s, affecting a wide thematic spectrum: enhancing population cultural level, tolerance and mutual respect, eradicating various kinds of prejudices and the fight against discrimination, health and healthcare, family values. The specificity of the phenomenon of Italian public service annonncement (PSA) involves drawing attention to the most acute problems of society and the search for their solutions. In addition, tools and means of influence result from current social trends and ongoing events. This makes it possible to assume that PSA, in addition to its main task - to regulate human behaviour model, is a kind of an expert system addressed by the individual in the search of his real self, which is the search of national and personal identity. The search for national identity for Italy is highly relevant both in the indicated period and today, due to a number of historical, ethnographic and cultural factors, as well as the linguistic picture of the country. Analysis of the topics of PSA, their implementation, methods and mechanisms of influence, as well as the effectiveness of a particular campaign in a certain period and conditions, provide an opportunity to draw certain conclusions about how the country is positioning itself at the European and world level.